Monitoring funkcional'noj podgotovlennosti vysokokvalificirovannych sportsmenov i soveršenstvovanie programmnogo obespecenija v processe trenirovocnych meroprijatij - Iordanskaya, F. A.; Abramova, T. F.; Tsepkova, N. K.; Buchina, E. V.; Malkin, R. V. (Vestnik sportivnoj nauki; Sports science bulletin, 2018)
The paper presents generalized data from years of research on the monitoring of various aspects of the preparedness of elite players (hockey, volleyball, beach volleyball). A program for monitoring the health and functional condition of athletes developed for the 2008 Olympics and tested in practice is described.